Interactive three-dimensional carving using a combined voxel and mesh representation - Williams, Jeffrey A (University of Ottawa (Canada), 2008)
This thesis proposes an approach to provide a visually realistic interactive simulation of the effect of removing rigid bounded volumetric portions of a 3D object. The approach processes the volume removal at sufficient rates for realistic real-time rendering, while minimizing the error caused during volume removal operations. We refer to these volume removal operations as 3D carving. 3D carving is particularly applicable to the computer simulation of bone-surgery medical procedures performed with a motorized burr tool; however the methods and algorithm presented are generic enough to be used for other purposes such as 3D modeling, destructible objects in 3D games and others. Our approach represents the volume of the object being carved using voxels while displaying the object to the user using an associated polygonal mesh. We use the Ball-Pivoting Algorithm---which has been traditionally used to generate a triangle mesh from a point cloud---to generate the mesh associated with the voxels, but we present a novel extension to the algorithm, the Dynamic Ball-Pivoting Algorithm, so that local changes to the voxel set only require local changes to the mesh, whereas the standard algorithm would require a global remeshing. We demonstrate how to apply 3D and 2D textures simultaneously to provide separate external and internal textures for objects that have different skin and internal appearances, which increases the realism of the visualization. We provide measurements of the performance and accuracy of our approach.
Keywords: Computer Science.